A Catalytic Approach to Quinoline Fused Lactones and Lactams from Glycine Derivatives. Issue 16 (18th November 2015) - Huo, Congde; Yuan, Yong; Chen, Fengjuan; Wang, Yajun
Abstract: A dual catalyst system [copper(II) chloride‐sulfuric acid, (CuCl2 ‐H2 SO4 )]‐promoted aerobic oxidative reaction of glycine derivatives with 2, 3‐dihydrofurans or 2, 3‐dihydropyrroles has been explored, affording an efficient synthesis of high value quinoline fused lactones and lactams. The application of this new methodology to the synthesis of a bioactive C ring extension analogue of luotonin A has been accomplished in a concise three‐step sequence. Abstract :